2016
DOI: 10.1038/eye.2016.168
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour intraocular pressure and ocular perfusion pressure characteristics in newly diagnosed patients with normal tension glaucoma

Abstract: Purpose To determine the mean 24-h intraocular pressure (IOP) and mean ocular perfusion pressure (MOPP) characteristics of newly diagnosed, previously untreated, Caucasian, normal tension glaucoma (NTG) patients and to identify relationships between these features and visual field (VF) loss at diagnosis. Methods Consecutive newly diagnosed NTG patients underwent 24-h habitual IOP and blood pressure (BP) monitoring. Parameters from pooled measurements obtained in the sitting (0800-2200 hours) and supine (1200-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…In a separate retrospective study, Sung et al [4] also found that greater 24-h MOPP fluctuation is associated with the increased rate of NTG progression. In contrast, Quaranta et al found no association between 24 h MOPP and VF damage in Caucasian NTG patients [10].…”
Section: Introductionmentioning
confidence: 87%
“…In a separate retrospective study, Sung et al [4] also found that greater 24-h MOPP fluctuation is associated with the increased rate of NTG progression. In contrast, Quaranta et al found no association between 24 h MOPP and VF damage in Caucasian NTG patients [10].…”
Section: Introductionmentioning
confidence: 87%
“…Evidence suggests that glaucoma is a multifactorial disease, and so an individual's susceptibility is likely related to a combination of factors, including the eye's optic nerve head (ONH) structure and biomechanical properties, 1,2 tissue and cellular responses to IOP and cerebrospinal fluid pressure (CSFP), [3][4][5][6][7][8][9][10] and ocular perfusion pressure (OPP). [11][12][13][14] Complicating things even further, racial differences 15,16 and changes with age 15,17,18 or exposure to chronic IOP elevation/glaucoma [18][19][20] likely influence these factors as well. 2,21 CSFP has been hypothesized as a driving factor in glaucoma, as it provides a counter-pressure to IOP, but only at the ONH.…”
mentioning
confidence: 99%
“…One possible explanation for this finding is that OPP is much lower at night with less variability, which may explain why the relationship was significant for waking hours, but not for sleeping hours. In addition, past studies have suggested that ocular blood flow is related to the level of visual stimuli, 5 , 8 , 23 , 24 and pulsatile ocular blood flow is an important factor in the ocular pulse amplitude (OPA). Hence, we might expect that IOP transient impulse and OPP will be larger during periods of intense activity, when visual system is stimulated, blood flow (and OPA) are high, and blinks and saccades are frequent.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Intraocular pressure (IOP) is a known risk factor for both the development and progression of glaucoma. 2 , 3 Lowering IOP is the only clinically proven method to prevent glaucoma and slow disease progression, although some patients develop glaucoma at statistically normal IOP levels, 4 , 5 and others continue to progress even after IOP is lowered. 6 Diurnal IOP fluctuations, measured hourly, have been reported as higher in glaucoma patients in some studies 7 and may be predictive of disease progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation